Estética da confissão em fanny hill e teresa filósofa: o papel da pornografia na ascensão do romance moderno - Morais , João Batista Martins de (2014)
The licentious novel of the so-called "Century of Lights" was allied to the epistolary method of composition by which an atmosphere of intimacy is created and which favors the emergence of a discourse of secrecy; this atmosphere, a priori, is conducive to the individual exposure and confession of secrets. In this context, the ideas of the philosopher John Locke (2012) ― inserted in this study ― were influential in placing the sensorial experience in the first sphere of the means by which the individual is led to understanding, and thereby giving the body greater importance in the construction of the individual identity. Following Ian Watt's (2010 ) conclusion that the novel is consolidated when the narrative resources used in it become subordinated to a moral intention, and Foucault's (2006 ) assertion that the practice of religious confession gradually lifted sex to a privileged dimension of individual inner truth, our research aims to analyze the impact of writing of the self in the consolidation of the novelistic genre, taking as a corpus for this thesis two influential pornographic works of the period: Fanny Hill or Memoirs of a woman of pleasure (1749, John Cleland / England) and Theresa, Philosopher, or Memoirs to serve as the story of Father Dirrag and Miss Eradice (1748, Jean-Baptiste de Boyer , Marquis d' Argens / France). In these novels, the moral is problematized by an incursion into the obscene, and in confessions in which the characters recall learning processes from two relevant axes in the literature of the Enlightenment: pleasure (Fanny Hill is an apprentice prostitute) and philosophy (Theresa is an apprentice libertine). In this study, we have tried to show that the discourse on sex in the eighteenth century pornographic novel is endowed predominantly with what we have chosen to name aesthetics of confession, and that this resulted in important developments in the characteristics that the novel took in the eighteenth century.